Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Critical Thinking pada Materi Nafsu Syahwat dan Ghadlab - Widyaningrum, Retno; Izzati, Leni Nurul (MA'ALIM: Jurnal Pendidikan Islam, 2023)
Student Worksheet are one of the teaching materials that are the teacher's choice. Student Worksheet can facilitate the delivery of messages from teachers to students, improve the ability to think, feel, pay attention, increase students' interest in learning, and the learning process run as expected. Based on the results of review at MA Muhammadiyah 1 Ponorogo in learning activities the teaching materials used were printed teaching materials available in schools. Assignments given to students based on textbooks used during the learning process. Student Worksheet cannot be fully implemented, whereas if using Student Worksheet in learning activities, the Student Worksheet used is still in a simple form containing only questions that must be worked on by students. This study aims to: (1) Determine the feasibility of Student Worksheet based on Critical Thinking on Lust and Ghadlab materials. (2) Knowing students' responses to Critical Thinking-based Student Worksheet on Lust and Ghadlab materials. (3) Knowing the effectiveness of Student Worksheet based on Critical Thinking on Lust and Ghadlab materials.This type of research uses a development research methodology (Research and Development/ RND). With reference to the ADDIE research model, namely Analysis, Design, Development, Implementation, and Evaluation. The subjects of data collection in this study were 3 validators and class X students of MA Muhammadiyah 1 Ponorogo. The research instruments were validation sheets, student response questionnaires, and test. The results of the study show that: (1) LKPD based on Critical Thinking is declared valid after repair or revision. LKPD has met the criteria according to the Aiken's V test and obtained a validation coefficient of 1.00. So that LKPD based on Critical Thinking is suitable for use in learning. (2) LKPD based on Critical Thinking gets a good response from students with an average response value of 15% of students answering quite agree, 31% answering agree, and 60% answering strongly agree, then student responses to LKPD based on Critical Thinking categorized as good. (3) LKPD based on Critical Thinking is effectively used in learning. In the results of the Paired T Test the significance generated is 0.000 and the N Gain test results obtain an average value of 0.6107, the level of effectiveness of LKPD based on Critical Thinking is categorized as moderate.